2013
DOI: 10.1590/s1516-18462013005000040
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre ausência do reflexo do músculo estapédio e presença de distúrbios do processamento auditivo (central)

Abstract: Objetivo caracterizar e relacionar os achados do reflexo acústico do músculo estapédio em indivíduos com diagnóstico de distúrbios do processamento auditivo (central). Métodos pesquisa transversal descritiva retrospectiva, submetida e aprovada pelo Comitê de Ética em Pesquisa, sob o protocolo nº 0047/11. Amostra constituiu-se de 83 prontuários de indivíduos de ambos os gêneros (57 masculino e 26 feminino) que apresentaram alteração na avaliação do processamento auditivo (central) associada à ausência do refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…However, if the frequencies of the acoustic reflex are analyzed individually, it is observed that a large number of children presented absence of the acoustic reflex at the frequency of 4000 Hz, in both the ipsilateral and contralateral pathways. This information is consistent with a study that compared the results of acoustic reflex measurement with the results of figure-background testing and temporal ordering, which also found a higher number of altered acoustic reflex results at this frequency 31 . The occurrence of isolated absence of the acoustic reflex at 4000 Hz is high when compared with other frequencies.…”
Section: Figure 2 -Total Number Of Acoustic Reflexes With Alterationssupporting
confidence: 90%
“…However, if the frequencies of the acoustic reflex are analyzed individually, it is observed that a large number of children presented absence of the acoustic reflex at the frequency of 4000 Hz, in both the ipsilateral and contralateral pathways. This information is consistent with a study that compared the results of acoustic reflex measurement with the results of figure-background testing and temporal ordering, which also found a higher number of altered acoustic reflex results at this frequency 31 . The occurrence of isolated absence of the acoustic reflex at 4000 Hz is high when compared with other frequencies.…”
Section: Figure 2 -Total Number Of Acoustic Reflexes With Alterationssupporting
confidence: 90%
“…According to the literature, the action of the superior olivary complex regulates the contraction of intratympanic muscles and the skills involved in CAP. Thus, it is possible that changes in the acoustic reflex results stimulate the occurrence of alterations in auditory processing skills (19) . Besides the inner ear protection, the stapedial reflex arc is also related to the ability of sound location, speech detection, improved listening ability, improved speech intelligibility and noise attenuation in speech understanding (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that changes in the acoustic reflex results stimulate the occurrence of alterations in auditory processing skills (19) . Besides the inner ear protection, the stapedial reflex arc is also related to the ability of sound location, speech detection, improved listening ability, improved speech intelligibility and noise attenuation in speech understanding (19) . It should be emphasized that the history of recurrent otitis, so prevalent in individuals with altered auditory skills (20) , may justify the alterations of contralateral acoustic reflex.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing acoustic reflexes in the pre- and post-phases ( Table 3 ), we found no statistical difference, but it was possible to observe an improvement in responses post-operatively. The absence of the acoustic reflex is an indication of changes in the middle ear; however, due to the high complexity of the neural mechanism involved, the presence of increased threshold values and/or the absence of the acoustic reflex in individuals with tonal auditory thresholds within the standard normality may be associated with the presence of changes in language and auditory processing [ 36 ].…”
Section: Discussionmentioning
confidence: 99%